PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN BAN MOBIL - Anjelita Sari Ulfanur; Yayuk Yuliana (Bajang Institute, 2021)
the objective of the research was to determine the influence of price and product quality on influence on consumer buying interest Accelera brand car tires in the shop Tkb Group Indonesia Medan. The population in this study were Indonesian Tkb Group consumers who were interested in buying Accelera brand car tires, the sampling technique used purposive sampling, so that the number of samples obtained was 97 respondents. The data analysis technique used is validity and reliability. Data were analyzed using classical assumption test techniques, multiple linear regression analysis, t test of , F test and coefficient of determination (R 2) . The results of this study indicate that there is a significant and significant effect between price on buying interest and a positive and significant influence between product quality on buying interest. The results of this study indicate that price and product quality are determinants of consumer buying interest in Accelera brand car tires at the Tkb Group Indonesia Store Medan. Where the value of the t-test variable x1 (price) is 2.620, the value of the t-test variable x2 (product quality) is 5.118. 45.274 F value and the coefficient of determination (R 2 ) of 0.491 which means that the price and quality of products has the effect of 49.1% the rest of 50.9% are other variables that are not described in this study.